The Role of Database Teachers in Increasing the Learning Interest of Class XI PPLG Students - Brama Kumbara; Dwi Maryono; Dwi Esti Wardani (Journal of Informatics and Vocational Education, 2024)
It is very important for teachers to foster students' interest in learning at Vocational High Schools (SMK). Without interest in learning, students will not really learn. In this research, a qualitative descriptive approach was used. To collect data, observation and interviews were used. Analysis is carried out by conducting analysis during data collection, namely inductively using descriptive data through systematic logical reasoning to ensure the validity of the data; then, after the data is collected, data analysis is carried out using triangulation techniques (comparing/checking, checking the validity of the data), using information observed from interviews and observations. The results of research in the field show that database teachers can help increase interest in learning by developing learning plans that take into account students' conditions and interests, integrating learning variations with individual approaches, openness, exemplary, functional, and providing motivation. Research also finds that teachers can help their talents and interests in learning by providing facilities and infrastructure that help them learn. Research also finds that teachers can help improve the influence of the environment, friends, as well as the conditions of students and their families both from school and from the students themselves. These are some of the things that can hinder students' interest in learning, while teachers must be responsible as Skills Program Coordinators, thereby creating a lesson schedule which is not quite right. Keywords: Interest in Learning, Qualitative, Teacher's Role, Vocational School